A Systematic Literature Review on Islamic Expenditures - Sobiyanto, Ahmad; Bustamil, Bustamil; Handayani, Tri; Hamzah, Muhammad Zilal (IAIN Ponorogo, 2023)
The purpose of this study is to identify past research trends on Islamic spending, evaluate research collaborative relationships, and identify future research directions.It uses 14 articles published between 2003-2022 about Islamic Expenditures indexed in Scopus (Q1-Q4) using a qualitative and quantitative approach, the Bibliometric method and Systematic Literature Review (SLR). This study uses VosViewers software and Publish or Perish. It is known that the author who has the most publications on Islamic Expenditure is U.H. Umar. The article with the most citations was the article entitled